A review on phytochemicals, pharmacological activities, drug interactions, and associated toxicities of licorice (Glycyrrhiza sp.). Issue 4 (31st August 2021) - Husain, Islam; Bala, Kiran; Khan, Ikhlas A.; Khan, Shabana I.
Abstract: Since the beginning, human beings have consistently been using plants and their components for the prevention and treatment of various ailments. However, in the last few decades, plant‐based medicines and health supplements are gaining more acceptability and rapid popularity. Licorice ( Glycyrrhiza sp.) is a terrestrial herb belonging to the family Fabaceae and primarily cultivated in European, Middle Eastern, and South Asian countries. Ethnomedicinal uses of licorice have frequently been described in the world's renowned medical systems, including Ayurveda, Unani, Chinese, Korean, Japanese, African, and European traditional medical systems. To date, 30 species of licorice are known, and among them, G . glabra, G . inflata, and G . uralensis are significantly explored for nutritional and pharmacological benefits. The wide range of commercially available products, including herbal preparations, health supplements, cosmetics, and food and feeds preparations use licorice as active ingredient. Glabridin, licochalcone A, glycyrrhizin, and 18‐glycyrrhetinic acid are the notable phytochemicals isolated from licorice and immensely explored for biological and pharmacological activities. Nevertheless, the excessive intake of licorice has also been associated with a wide spectrum of adverse effects on human health. Among them, several are reported to be mediated by modulation of drug‐metabolizing cytochrome P‐450 enzymes. In the present review, we provide a comprehensive description of the current knowledge of licorice, including historical development, phytoconstituents, species‐specific marker metabolites, herb–drug interaction, pharmacological uses, food additive application, and toxicities. We believe this review will provide excellent information to physicians, researchers, and personnel of different scientific regulatory bodies. Abstract : An overview of licorice application and its health benefits